Primary Pulmonary Resection in Madagascar: Indication and Results (London Journal of Medical and Health Research, 2025)
Introduction: Primary pulmonary resection is defined as the surgical ablating or endoscopic of an entire lobe called lobectomy or an entire lung called pneumonectomy. Our objective is to describe the indication for a primary pulmonary resection and to research the morbidity and mortality factors of primary pulmonary resection at the Joseph Ravoahangy Andrianavalona Antananarivo University Hospital.Method: This is a retrospective descriptive and analytical study of 216 patients hospitalized in the thoracic surgery department at the Joseph Ravoahangy Andrianavalona Antananarivo University Hospital (CHU-JRA), from January 1, 2015, to December 31, 2023, who underwent primary pulmonary resection.Results:We collected 216 patients with a male predominance (73,6%) and a median age of 33. Post-tuberculosis pulmonary destruction is the main indication for resection in 53,24% cases, followed by a cavernous lesion of pulmonary aspergillosis in 24,07% cases then tumor mass in 18,06% and the nodular lesion in 4,63% cases. We realized a lobectomy in 71,29% of cases and a pneumonectomy in 28,71%. The complications found are dominated by pneumothorax, prolonged bubbling, pleural empyema, bronchopleural fistula, bleeding, recurrent paralysis, septic shock and cardiac rhythm disorder. The mortality rate is 8,33% cases. severe factors were found notably: undernutrition with IMC ? 18 kg/m2 (RR= 5[2,1-11,7]), hemorrhagic shock (RR=9,3[3,7-13,3]), septic shock (RR=13,3 [4,6-28,4]), cardiogenic shock (RR=8,5[3,7-12,3]), pleural empyema (RR=8,5[3,8 -13,6], bronchopleural fistula (RR=6,7[2,9-15,3]).
Keywords: urogenital abnormality; anorectal malformation; Creatinine; Electrolytes; Urea.; Biochemical parameters; dengue patients; serum albumin; serum ALT; Indigenous Knowledge; traditional medicine (tm); herbs; nso; bakweri; efficacy; inefficacy; traditional healers; herbal remedies; medical anthropology.; Arrhythmia; Atrial flutter; Vagal maneuvers; Electrical cardioversi; Surgery; tuberculosis; Aspergillome; Empyema; Lobectomy; Pneumonectomy